2009
DOI: 10.1002/ajp.20677
|View full text |Cite
|
Sign up to set email alerts
|

The feeding ecology and activity budget of proboscis monkeys

Abstract: A group of proboscis monkeys (Nasalis larvatus) consisting of an alpha-male, six adult females, and several immatures was observed from May 2005-2006. We collected over 1,968 hr of focal data on the adult male and 1,539 hr of focal data on the six females in a forest along the Menanggul River, Sabah, Malaysia. Availability and seasonal changes in plant species consumed by the focal monkeys were determined by vegetation surveys carried out across an area of 2.15 ha along 200-500 m trails in riverine forest. A t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
119
2
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 144 publications
(134 citation statements)
references
References 33 publications
4
119
2
3
Order By: Relevance
“…Proboscis monkeys are the largest foregut-fermenting primates and ingest a diet consisting of various proportions of leaves and fruit [21]. They are endemic to Borneo and inhabit mangroves, swamps and riverine forests.…”
Section: Introductionmentioning
confidence: 99%
“…Proboscis monkeys are the largest foregut-fermenting primates and ingest a diet consisting of various proportions of leaves and fruit [21]. They are endemic to Borneo and inhabit mangroves, swamps and riverine forests.…”
Section: Introductionmentioning
confidence: 99%
“…We found that individuals appeared to select sleeping trees with more mature leaves, unripe and ripe fruits than surrounding trees. By referring to a previous study conducted in the Kinabatangan region [Matsuda et al, 2009] as well as to our feeding records at sleeping sites, we noticed that more than 80% of the trees (sleeping, surrounding and control) belonged to species that proboscis monkeys are known to consume. However, it is too early to be sure that food abundance is a significant factor in sleeping site selection, as we considered leaf, fruit and flower abundances for all tree species present in our plots, whether they were consumed or not by proboscis monkeys at that time.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies should investigate in depth the 'food proximity' hypothesis, by recording the distance between sleeping trees and the last and first feeding trees of the day. It is known that food availability, especially of fruits, influences proboscis monkeys' daily path lengths and activity budget [Matsuda et al, 2009[Matsuda et al, , 2014, and may impact their sleeping choices as well.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A large part of the species range is in peat swamp, an extremely threatened ecosystem [Prentice and Parish, 1991;Rieley et al, 1997;Harrison et al, 2007Harrison et al, , 2011Miettinen et al, 2012]. The subfamily Colobinae consists of predominantly leaf-eating primates [Chivers and Hladik, 1980;Oates et al, 1980;Kool, 1986;Duc et al, 2009;Matsuda et al, 2009] and has evolved gastro-intestinal adaptations to exploit this abundant resource [Bauchop and Martucci, 1968;Chivers, 1994]. A multi-chambered stomach containing a microbe suspension in the foregut, plus a capacious stomach chamber and elongated caecum simultaneously neutralize toxins and effectively break down plant wall cellulose, facilitating digestion of the high quantities of fibre, protein and vitamins generally contained within leaves and other less digestible foods [Bauchop and Martucci, 1968;Kay et al, 1976;Chivers, 1994;Kay and Davies, 1994;Tsuji et al, 2013].…”
Section: Study Speciesmentioning
confidence: 99%